Power and Ethics in State-Owned Enterprises: The Pertamax Adulteration Case through the Lens of Sharia Economic Law - Lia Yuliana; Antoni Julian (Nusantara: Journal of Law Studies, 2025)
This article analyzes the misuse of authority by officials of state-owned enterprises (BUMN) in the Pertamax fuel adulteration case from the perspective of Sharia Economic Law. The study employs a qualitative-descriptive method with a normative-juridical approach, drawing on primary and secondary legal materials, supported by documentation and literature analysis. The findings reveal that the act of fuel adulteration—mixing subsidized or lower-grade fuels with Pertamax for economic gain—is not only a violation of state regulations but also a breach of the amanah and maslahah principles in Islamic law. The abuse of authority by BUMN officials in this context indicates a failure to uphold public trust (al-amānah), justice (al-ʿadālah), and the public interest (al-maṣlaḥah al-ʿāmmah) as mandated by Sharia economic ethics. Such practices lead to market distortion, consumer losses, and potential macroeconomic instability, all of which are inconsistent with the maqāṣid al-sharīʿah framework. The study concludes that these actions should be categorized as gharar, khiyānah, and fasād, thereby necessitating systemic reform in the governance of BUMN and the energy sector. The academic contribution of this article lies in its comprehensive integration of modern legal-economic analysis with the principles of Islamic economic jurisprudence, offering a theoretical model for evaluating public sector violations through a Sharia lens. Furthermore, this study contributes to strengthening the legal and ethical foundations in the formulation of policies and regulations governing state-owned enterprises.